Production of Organic Fertilizer from Rice Husks and Cow Manure to Increase Crop Production in Leming Village - Muhtadi, Muhammad Fauzan; Alkusairi , Lalu Randi; Rizkillah, Muhammad Firman Haris; Listiani, Ulmi; Sarfina, Sarfina; Ramadhani, Novianda; Pazira, Ira; Duhita, Baiq Rizqi Amelia; Nur, Saufa Marwatin; Septiana, Nuraweni; Hemon, A. Farid (Pascasarjana Universitas Mataram, 2025)
Chemical-based fertilizers have become a significant issue in the agricultural sector of Leming Village, Terara District, East Lombok Regency. Excessive use of chemical fertilizers can lead to various negative impacts on the environment, human health, and agricultural sustainability. Observations on the use of chemical fertilizers in Leming Village indicate that the number of chemical fertilizer users remains high, along with a low level of public awareness regarding the harmful effects of these fertilizers. The 2025 KKN PMD Program of Mataram University in Leming Village aims to educate the community about the dangers of chemical fertilizers, provide an alternative in the form of organic fertilizer made from a combination of rice husks and livestock manure (cow dung), and train the community in producing organic fertilizer using these materials. In addition to these initiatives, the KKN PMD program also includes tree planting and seedling distribution, which will be utilized for compost application